2000
DOI: 10.2307/2648098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pregnancy intention on child development

Abstract: In this paper, we use data from the National Longitudinal Survey of Youth to investigate the empirical link between unintended pregnancy and child health and development. An important contribution of our study is the use of information on siblings to control for unmeasured factors that may confound estimates of the effect of pregnancy intentions on infant and child outcomes. Results from our study indicate that unwanted pregnancy is associated with prenatal and postpartum maternal behaviors that adversely affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
166
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(182 citation statements)
references
References 17 publications
11
166
2
3
Order By: Relevance
“…24 Data from 3,000 American families when the subjects were between 4 and 13 years of age, showed that unwanted pregnancy did not have significant effects on infant health or early child development. This was similar to the findings of a review of local health clinic records and other observations when the Prague subjects were of a similar age.…”
Section: Siblingsmentioning
confidence: 99%
“…24 Data from 3,000 American families when the subjects were between 4 and 13 years of age, showed that unwanted pregnancy did not have significant effects on infant health or early child development. This was similar to the findings of a review of local health clinic records and other observations when the Prague subjects were of a similar age.…”
Section: Siblingsmentioning
confidence: 99%
“…The large majority of the research focused on unintended pregnancies has attempted to document the effects of pregnancy intention on the health and development of infants and children-with poorer comparative outcomes found among children resulting from unintended pregnancies. [12][13][14][15][16][17][18][19][20] The literature exploring the effect on the well-being of women who continue these unintended pregnancies to term is comparatively thin. Gipson et al highlighted the "scarcity of studies on the effects of unintended pregnancy on the physical and mental health of men and women."…”
mentioning
confidence: 99%
“…Vários estudos apontam que crianças frutos de uma gestação não planejada teriam maior probabilidade de apresentar dificuldades quanto ao seu desenvolvimento 10,11,[13][14][15][16] . Contudo, a originalidade deste estudo constitui-se na discriminação de dois grupos diferentes, indicando um risco maior quando além de não planejada a gravidez não é aceita até o quarto mês.…”
Section: Discussionunclassified